Cooperation, coopetition and innovation - Daidj, Nabyla, 1964- (Innovation, entrepreneurship, management series. Innovation and technology set, 2017)
In presenting the concepts and the logical structure of the reasoning offered by game theory and their applications, the book explains the rational process of decision making in the framework of firm management and market competition. The book will expose both general teachings and a comprehensive analysis applied to specific case studies of various sectors of the economy.